"A Salute to the Bandido": A Political Ecology of Voice Exploration into Peru's Freedom of Voice Surrounding Hydrocarbon Development. Issue 6 (3rd June 2018) - Gonzalez, Adrian
ABSTRACT: This paper sets out to evaluate the freedom of voice for Peruvian stakeholders affected by hydrocarbon development. This occurs through the utilization of a political ecology of voice (PEV) theoretical framework based upon the theory of voice by Albert Hirschman and political ecology. PEV can be defined as the study of economic, political, social, and geographical factors over a specific time period and their impact upon the use of voice by stakeholders. Peru's case study was focused on its main oil-producing Loreto Region and incorporated evaluation of hydrocarbon voice mechanisms (prior consultation and environmental impact assessments) supported by interview testimony of stakeholders and state officials. PEV analysis reveals a political environment which is dangerous, inflexible, and intolerant of Peruvian stakeholders voicing over hydrocarbon development. This is due to the state's zealous pursuit of its " selva (rainforest) hydrocarbon and development vision" which severely undermines Peruvian stakeholder's freedom of voice.